Barriers to Exercise in Type 1 Diabetes Patients and the Impact of Aerobic and Anaerobic Exercises on Blood Glucose Management: A Current Literature Review - Lissak, Karina; Nowińska, Bianka; Bińczyk, Wiktoria; Dróżdż, Olgierd; Siudek, Bartosz; Wiśniewska, Anna; Konopka, Agata; Szczepaniak, Zuzanna; Orzeł, Milena; Orzeł, Bartłomiej; et al. (Quality in Sport, 2024)
Engaging in regular physical activity (PA) is crucial for managing type 1 diabetes (T1D) effectively. PA helps reduce the risk of cardiovascular disease (CVD), lower total daily insulin requirements, improve endothelial function, enhance muscular strength, and boost psychological well-being and quality of life. However, individuals with T1D tend to engage in PA less frequently than their healthy peers due to various barriers, with the fear of hypoglycemia (FOH) being a significant factor that impacts quality of life and diabetes outcomes. Understanding these barriers can increase awareness, improve comprehension, and enhance better support from non-diabetology specialists. This article aims to review the current literature on the primary limitations to regular PA, including continuous glucose management (CGM), in individuals with T1D. Additionally, we explore the impact of various types of PA on blood glucose management and overall well-being.